ETR 300 : Spice Islands Enterprise / Ahmad Faruq Ahmad Zahran ... [et al.] - Ahmad Zahran, Ahmad Faruq; Ibrahim, Ismail; Yaakup, Hairil Syukr; Abdul Halil, Amilia; Azaheri, Nurul lzwani (2003)
Nowadays, most of the people in Malaysia are using spice (rempah) as the main ingredient in their food. Some of them are using spice for health purpose. Something amazing about spice is all races are eating it. Therefore, we take this opportunity to enter in this kind of business. Our Business's name is 'Spice Islands Enterprise.' It focuses on different types of spice with the different taste, quality and price. Actually, our business is formed by partnership. There are five partners involved which consists of Mr. Ahmad Farug B. Ahmad Zahran as a General Manager, Mr. Ismail B. Ibrahim as an Administration Manager, Miss Amilia Bt. Abdul Halil as an Operating Manager, Miss Nurul Izwani Bt. Azaheri as a Marketing Manager and Mr. Hairil Syukri B. Yaakup as a Financial Manager. Of course, all partners have a very good and appropriate academic qualifications and experiences in working. Rather than that, we have seven workers. One worker is under marketing manager, five workers are under operating manager and another one is work for financial worker.